Long-Term Potentiation at CA3–CA1 Hippocampal Synapses with Special Emphasis on Aging, Disease, and Stress - Kumar, Ashok (Frontiers in Aging Neuroscience, 2011)
Synaptic plasticity in the mammalian central nervous system has been the subject of intense investigation for the past four decades. Long-term potentiation (LTP), a major reflection of synaptic plasticity, is an activity-driven long-lasting increase in the efficacy of excitatory synaptic transmission following the delivery of a brief, high-frequency train of electrical stimulation. LTP is regarded as a principal candidate for the cellular mechanisms involved in learning and offers an attractive hypothesis of how memories are constructed. There are a number of exceptional full-length reviews published on LTP; the current review intends to present an overview of the research findings regarding hippocampal LTP with special emphasis on aging, diseases, and psychological insults.